Analysis of profitability of chicken egg businesses in Randangan District, Pohuwato Regency - Nasrul, Muhammad; Nooyo, Irwan (AGRICOLA, 2025)
The aim of this research is to determine income analysis, profitability analysis, marketing margin and marketing efficiency of chicken egg businesses in Randangan District, Pohuwato Regency. This research was carried out for 3 months, starting from August 2024 to October 2024. The data collection technique in this research uses Stratified Random Sampling, namely a sampling technique used to take heterogeneous samples randomly, divided into layers that are completely separated from each other and each layer (strata) can be taken randomly. In this study, the determination of respondents was carried out deliberately (purposively) with a total population of 14 people, namely 2 chicken egg entrepreneurs, 2 collecting traders, and 10 retail traders. The analysis used is revenue analysis, profitability analysis, marketing margin, and marketing efficiency. Research analysis shows that the income obtained from the chicken egg business in Randangan District is IDR 510,137,889/month. Gross Profit Margin (GPM) value 19.52%, Net Profit Margin (NPM) value of 16.19%, and Return On Investment (ROI) value of 5.59%. The marketing margin for the chicken egg business in Randangan District, Pohuwato Regency at marketing channel level I is IDR 14,500/shelf and at marketing channel II it is IDR 9,500/shelf. The marketing channel for the chicken egg business in Randangan District, Pohuwato Regency has an efficiency value of 3.61% for collectors and 1.72% for retailers.